2000
DOI: 10.1002/1529-0131(200011)43:11<2428::aid-anr9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cerebral involvement in patients with active neuropsychiatric systemic lupus erythematosus by the use of volumetric magnetization transfer imaging

Abstract: Our results indicate that volumetric MTI analysis detects cerebral changes in the active phase of NPSLE. The abnormalities in the brain parenchyma of patients with chronic NPSLE produced MTI values that were the same as those in patients with inactive MS. MTI values in the active phase of NPSLE differed from those in the chronic phase, which might reflect the presence of inflammation. These preliminary results suggest that MTI might provide evidence for the presence of active NPSLE. MTI might also prove to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…In these studies, NPSLE patients without visible abnormalities on conventional MR sequences had a lower MTR peak height compared to healthy controls and SLE patients without neuropsychiatric symptoms (12,16,17). Furthermore, these cross-sectional studies found correlations between MTR peak height and psychiatric, neurologic, and cognitive function, which suggests that the MTR peak height is clinically relevant (17).…”
Section: Dicussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In these studies, NPSLE patients without visible abnormalities on conventional MR sequences had a lower MTR peak height compared to healthy controls and SLE patients without neuropsychiatric symptoms (12,16,17). Furthermore, these cross-sectional studies found correlations between MTR peak height and psychiatric, neurologic, and cognitive function, which suggests that the MTR peak height is clinically relevant (17).…”
Section: Dicussionmentioning
confidence: 78%
“…MTR histograms, normalized for tissue volume, were generated for the whole brain and for normal-appearing brain tissue. From these MTR histograms the peak height was calculated (12,16,17). The peak height of these histograms was used as a measure of cerebral lesion load (17).…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bosma et al (2000a, b) have applied MTI to the characterization of normal appearing brain tissue and the evolution of lesions in SLE. In one of their studies (Bosma et al 2000a), they used MTI to study MS and SLE patients with and without a history of NP involvement. Magnetization transfer ratio histograms were abnormal in NP-SLE and MS patients, and the authors suggested that these manifestations in the cerebral white matter could include focal areas of demyelination, and/or vasculopathy.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
“…Using MTI, a quantitative MRI technique that is sensitive to both macroscopic and microscopic CNS damage (4), abnormalities that had been invisible by conventional MRI were demonstrated in the brain parenchyma of NPSLE patients (5). Significant associations with parameters of neurologic, psychiatric, and neuropsychological function demonstrated the clinical relevance of these findings (6).…”
mentioning
confidence: 99%